ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL CERITA HIMPUNAN - Salsya Nurhalisya; Haerudin Haerudin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this research was to determine students error in solving the story problems of the Set which were analyzed based on Newman’s procedure. This type of research used a descriptive qualitative approach. The subject of this study were students of class VII.A in one of the Junior High School in Karawang Regency which consisted of 32 students. Data’s collection was using a test consisting of 2 question about the Set material and unsctructured interviews. Data analysis technique of this research consists of three steps there are data reduction, presentation of data, and conclusions. Based on research of this results showed that there were five types of errors made by students, there were reading error, comprehension error, transformation error, process skill error, and encoding error. The error that often made by students in the first question were encoding error. While in the second question were transformation error.